Ibn Rushd’s Middle Commentary on the Poetics, or the Ethical Education - Frédérique Woerther (22030829) (2024)
In his Talkhīṣ Kitāb Arisṭūṭālīs fī l-Shiʿr (“Middle Commentary on Aristotle’s Poetics”) Ibn Rushd (Averroes, d. 595/1198) strictly defines poetic statements (al-aqāwīl al-shiʿriyya) as imaginative (mutakhayyila) statements that imitate the good and the evil, and aim at inciting people to virtue and deterring them from vice. Yet the traces of the Aristotelian ethical doctrine in this Commentary are not restricted to this link to virtue ethics, as the entire text follows at different levels the division between virtue/vice and good/evil. Ibn Rushd also refers to the teaching of ethics when discussing the object of poetic imitation (al-tashbīh wa-l-muḥākāt), the different natures he distinguishes among poets, and the genres of panegyric (madīḥ) and satire (hijāʾ). However, recent scholarship tends to view the Poetics in the Islamic context as a fundamentally logical treatise. Following the Alexandrian tradition, the falāsifa sought, at least since al-Fārābī (d. 339/950), to justify and explain the position of the Poetics in the Organon by defining, for example, the logical and psychological mechanisms of the poetical syllogism. More specifically, philosophers drew parallels between the role of imagination (takhayyul) in the poetical context and the role of assent or conviction (taṣdīq) in the other logical arts, and in particular in the Rhetoric (al-Khiṭāba). The purpose of this contribution is to demonstrate that the Poetics, according to Ibn Rushd, is a treatise that combines logic and ethics and determines in that respect the conditions and the rules of a practical education of the citizens. Like the rhetoric whose political value was already determined, poetics also plays a role in defining the nature and the content of the poetical statements that are to be employed in order to encourage people to virtuous actions – that is, the very condition for a virtuous political, and thus, a happy life. Straddling between logic and ethics, poetry is therefore fundamentally political. Other Information Published in: Journal of Islamic Ethics License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1163/24685542-20240011 Volume and issue information: Vol 8 No. 1-2 (2024): December 2024